TENURIAL REFORM AS ALTERNATIVE CONFLICT MANAGEMENT AND TO ALLEVIATE POVERTY OF COFFEE SMALLHOLDERS PLANTATION IN RURAL COMMUNITY - Mustapit Mustapit (UNEJ e-Proceeding, 2012)
Tenurial reform concerns the terms on which the operational holding is held and worked, and seeks to eliminate those aspects of the tenurial relationship, or the form of operational holdings, that are held to dull incentives, reduce the wherewithal to invest and impede efficiency, and so prevent the emergence of an efficient, dynamic and growing agriculture. This study aims to analyze the dynamics of protected forest management by surrounding community. Overlapping on forest management by Perhutani as the state enterprise for conservation function and by village community as a community Sidomulyo for coffee plantations until now does not cause conflict. This condition is due to the access mechanism and the distribution of benefits among the parties. It can be seen as tenure reform, which was to serve as an alternative conflict management while increasing household incomes and alleviating rural poverty.